Adaptive morphology of the heart of Southern-Fur-Seal (Arctocephalus australis - Zimmermamm, 1783) - Guimaraes, Juliana P.; Mari, Renata B. [UNESP]; Le Bas, Alfredo; Watanabe, Ii-Sei (Wiley-Blackwell, 2014)
The Southern-fur-seal belongs to the order Carnivora, suborder Pinnipedia, and Otariidae family. This species inhabits aquatic and terrestrial environments, thus presenting important morphophysiological adaptive changes, especially in the cardiac system. For this purpose, Southern-fur-seal (Arctocephalus australis) hearts were used from animals that died from natural causes. Gross morphology observations were supported by light, scanning and transmission electron microscopy. The heart was long and flat; it was lined by pericardium and partly covered by lungs. Structurally, atrium and ventricle muscle fibers exhibit typical features of cardiac fibers revealing myofibrils bundles, mitochondria, plate-shaped junctions, anastomosis between myofibrils bundles, and electron-dense granule natriuretic around the nucleus and mitochondria of atrium muscle cells. The Southern-fur-seal heart was structurally similar to other mammals; however, it presented morphological changes that assist in their adaptation to their environment.
Keywords: mitochondria; diving; SEM; cardiac muscle cells; pinnipeds; TEM